ETHICS EXPERTISE FOR HEALTH TECHNOLOGY ASSESSMENT: A CANADIAN NATIONAL SURVEY. (28th April 2014) - Bond, Kenneth; Oremus, Mark; Duthie, Katherine M.; Griener, Glenn G.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The aim of this study was to identify individuals with expertise in ethics analysis in Canada, who might contribute to health technology assessment (HTA); to gauge these individuals' familiarity with, and experience participating in, the production of HTA. Methods: A contact list was developed using the Canadian Bioethics Society membership list and faculty listings of Canadian universities, bioethics centers, and health agencies. An eighteen-question email survey was distributed to potential respondents to collect data on demographic information, education and work experience in applied ethics, and involvement in HTA. Results: The survey response rate was 52.8 percent (350/663). Respondents worked primarily in academic institutions (50.4 percent) or hospitals (15.4 percent). Many respondents (83.1 percent) had education, formal training, or work-related experience in practical ethics related to health care, with many having a doctorate (34.5 percent) or master's degree (19.0 percent). One quarter (24.5 percent; n = 87) of respondents indicated they had been involved in an analysis of ethical issues for HTA. Almost two-thirds (65.4 percent; n = 165) of those who had not previously participated in ethics analysis believed they might usefully contribute to an analysis of ethical issues in HTA. Experts who have conducted ethics analysis in HTA had more than twice the odds of having education and training in ethics and a PhD than those who might contribute to ethics analysis. Conclusion: Many people have contributed to ethics analysis in HTA in Canada, and more are willing to do so. Given the absence of a reliable credential for ethics expertise, HTA producers should exercise caution when enlisting ethics experts.